Development and Psychometric Evaluation of the Brief HIV Knowledge Questionnaire - Carey, Michael P. (2002)
This research evaluated the psychometric properties of a brief self-report measure of HIV-related knowledge, the HIV-KQ-18. Low-income men and women (N = 1019) responded to 27 items that represented the domain of interest. Item analyses indicated that 18 items, with item-total correlations ranging from .24 to .57, be retained. Additional analyses demonstrated the HIV-KQ-18’s internal consistency across samples (alphas = .75 to .89), test-rest stability across several intervals (rs = .76 to .94), and strong associations with a much longer, previously validated measure (rs = .93 to .97). Data from three clinical trials indicated that the HIV-KQ-18 detected knowledge gains in treated participants when compared to untreated controls. We conclude that the HIV-KQ-18 is internally consistent, stable, sensitive to the change resulting from intervention, and suitable for use with low-literacy populations.